Pickering nanoemulsions and their mechanisms in enhancing oil recovery: A comprehensive review - Adil, M. (Elsevier Ltd, 2022)
The key mechanisms in enhancing crude oil recovery include the reduction of interfacial tension (IFT) between the trapped crude oil and the injected flooding solution, the wettability alteration of the reservoir rocks, in-situ emulsification, pore plugging, mobility control, disjoining and capillary pressures, miscibility improvement, etc. Recently, Pickering nanoemulsions have emerged as attractive flooding fluids that can positively alter all the above mechanisms and, thus, provide an improved oil recovery relative to other tertiary methods. The nanoparticles (NPs) used to stabilize Pickering nanoemulsions must be carefully selected and engineered in order to impart the desired characteristics (e.g., stability, emulsion type, droplet size, zeta potential, etc.). Yet, the relationship between the efficacy of Pickering nanoemulsions in enhancing oil recovery and their characteristics is very complex and not fully understood. Additionally, the oil recovery enhancement mechanisms are quite complex and governed by several interrelated factors. Therefore, this article provides a state-of-the-art review of the formulations and applications of Pickering nanoemulsions for enhancing the recovery of crude oil, with a focus on the recovery mechanisms. Relevant recent studies on the topic have been analyzed and assessed in order to provide insights into the achieved progress and to highlight the remaining obstacles and challenges. Future research work to address the key obstacles and challenges has been proposed. Â© 2022 Elsevier Ltd